Ocular Point-of-Care Ultrasound in the Pediatric Emergency Department. Issue 3 (March 2019) - Seguin, Jade; Le, Cathie-Kim; Fischer, Jason W.; Tessaro, Mark Oliver; Berant, Ron
Abstract : Objective: Point-of-care ultrasound has become an important adjunct for diagnostic assessment in pediatric emergency medicine. In this case series, we demonstrate how ocular point-of-care ultrasound is used to correctly diagnose ocular pathologies and to expedite care. Methods/Results: We present a series of cases in which the point-of-care ultrasound ocular examination proved valuable in the timely diagnosis of pathologies involving the lens, vitreous, retina, and retrobulbar segment of the eye. Conclusion: Point-of-care ultrasound may facilitate diagnosis in children with ocular complaints, even in young and uncooperative patients, and should be considered in children of all ages.